Endoscopic removal of a massive trichobezoar in a pediatric patient by using a variceal ligator cap: A case report and literature review - Lu, Dan; Berglund, Björn; Xia, Yi; Jain, Ajay; Gu, Qing; Ji, Feng (Frontiers in Medicine, 2022)
A trichobezoar is commonly formed in the gastrointestinal tract by ingestion of an individual’s own hair. A trichobezoar formed by hair and artificial materials constitutes a rare etiology scarcely reported in the current literature. A mixture with hair-like synthetic fibers not only increases the risk for trichobezoar formation but also makes it more difficult for endoscopic removal. Herein, we report on a case in which a trichobezoar, caused by the consumption of human hair and synthetic yarn, was successfully removed endoscopically with a variceal ligator cap without further complications for the patient. This case report aims to raise awareness among endoscopists that using a variceal ligator cap may be a suitable option in the management of large trichobezoars containing synthetic fibers.